Capacity limits of crosstalk-limited multi-core fiber systems - Domingues, Ana Margarida Filipe (2021)
Space division multiplexing (SDM) is mainly seen as a way to increase data throughput and handle the fact that the data capacity of single mode single core fiber (SMSCF) is reaching its limit. Transmissions with capacities in the order of petabit per second have already been demonstrated using multi-core fibers (MCFs) with single mode transmission in each core. The performance of these systems is limited by the intercore crosstalk (ICXT). This dissertation analyzes the impact of the ICXT as a constraining element of the capacity of coherent detection optical communication networks that use the flexible grid over the C-band. The total capacity of the link, which is given by the number of cores allowed of a weakly-coupled (WC) MCF for each modulation format, is imposed by the maximum mean ICXT power acceptable for the connection. Link impairments such as the wavelength dependence of ICXT power over the transmission band and the nonlinear interference (NLI) noise due to MCF non-linear effects are also considered in the analysis. The total data capacities for metro networks, regional networks and long-distance networks are assessed for a W-profile MCF supported communication links. Considering the impairments of the link as the wavelength dependence of ICXT power over the transmission band and the NLI effects, the total capacities of 483.84 Tb/s by 32-QAM, 430 Tb/s by 32-QAM and 206.08 Tb/s by 4-QAM are achieved for the metro (represented with a link distance of 50 km), regional (represented with a link distance of 500 km) and long-distance networks (represented with a link distance of 5000 km), respectively.